2018
DOI: 10.20546/ijcmas.2018.710.180
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Various Phytoextract against Detected Seed Mycoflora of Groundnut

Abstract: The several types of oil including: aromatic roasted peanut oil, refined peanut oil, used in the manufacture of soap, medicinal emulsions, wool and silk, artificial leather. Groundnut oil is composed of mixed glycerides and contains high proportion of unsaturated fatty acids, in particular oleic (50-60 %) and linoleic acid (18-30 %). Different micoflora is causes heavy losses during storage of groundnut, keeping in a view the research were carried out with using different phytoextract against Alternaria altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The inhibitory effect of Aloe and Indian mulberry extracts against A. alternata was observed by other researchers. Bhosale et al [20] demonstrated antifungal activity of M. citrifolia extract in relation to Alternaria alternata, Aspergillus flavus and A. niger, isolated from groundnut (Arachis hypogaea L.) seeds. Saks and Barkai-Golan [11] who applied Aloe vera gel to control postharvest fungi: Penicillium digitatum, P. expansum, Botrytis cinerea and A. alternata, revealed that the gel suppressed germination and mycelial growth of all fungi, but P. digitatum and A. alternata were the most sensitive species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effect of Aloe and Indian mulberry extracts against A. alternata was observed by other researchers. Bhosale et al [20] demonstrated antifungal activity of M. citrifolia extract in relation to Alternaria alternata, Aspergillus flavus and A. niger, isolated from groundnut (Arachis hypogaea L.) seeds. Saks and Barkai-Golan [11] who applied Aloe vera gel to control postharvest fungi: Penicillium digitatum, P. expansum, Botrytis cinerea and A. alternata, revealed that the gel suppressed germination and mycelial growth of all fungi, but P. digitatum and A. alternata were the most sensitive species.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there are also some information about activity of Indian mulberry extract against plant associated fungi and bacteria. Under in vitro conditions the extract has been found antifungal against Alternaria alternata, Aspergillus flavus and A. niger, isolated from groundnut (Arachis hypogaea L.) fruits [20]. Morinda methanol extract inhibited the growth of Penicillium sp., Fusarium sp.…”
Section: Introductionmentioning
confidence: 99%